PENGARUH EKSPOR TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Dara Resmi Asbiantari; Manuntun Parulian Hutagaol; Alla Asmara (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2016)
Economic growth is a matter of the economy in the long term and is influenced by various factors. This study aimed to analyze the effect of the agricultural export, industrial export, mining export, import of capital goods, government spending and gross fixed capital formation to economic growth of Indonesia. The analytical method used was Ordinary Least Squares (OLS) with Cochrane-Orcutt method. This study uses secondary data quarterly time series from 2000 Q1 to 2016 Q1 which is obtained from the Ministry of Trade, the Central Bureau of Statistics, Bank Indonesia and the Capital Investment Coordinating Board. The results showed that on the first model to see the effect of the aggregate exports on economic growth show that imports of capital goods have a significant influence in the short term to economic growth. While in the long term, the variables that have a significant impact on economic growth is GFCF. While the second model to see the role of exports by sector to economic growth getting results that exports in the industrial sector has a significant influence both in the short-term and long-term to economic growth. It concluded that outward looking policies has an effective impact to be applied in Indonesia if the Government to develop exports in the industrial sector.